Firm age and the margins of international trade: Comparable evidence from five European countries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This note uses comparable representative data for manufacturing firms from five European countries (Germany, France, Italy, Spain, and the United Kingdom) to investigate the links between firm age and the participation of the firms in export, the share of exports in total sales, the number of countries exported to, and the participation in import. The big picture revealed is in line with the theoretical considerations. Older firms tend to be more often exporters and importers, they export to more different destination countries, and they export a higher share of their total sales in three out of five countries.
Keywords: F14; 330; Exports; imports; firm age; trade margins; EFIGE data